The humanities value chain: a framework for knowledge transfer in the modern university - Mooney Smith, Lisa (2009)
The Humanities Value Chain: A Framework for Knowledge Transfer in the Modern University PhD Abstract from Lisa Mooney Smith Nov 2009 ABSTRACT The research described in this thesis presents a body of material generated over four years of close observation of research and knowledge transfer practices in one Russell Group university institution. It attempts to contextualise knowledge transfer (hereafter KT) within the arts and humanities environment, as well as situate learning about the reception and adoption of KT with reference to the individual scholar and the organisation in which they operate. Within this context, little has been written explicitly about the character of the arts and humanities, and particularly the historical antecedence of the disciplines and their close relationship to current KT challenges.